Synthesis and characterization of cyano and isocyano complexes of bis(dithiolato) molybdenum using Me3SiCN: a route to a cyanide-bridged multimer to a monomer. (15th March 2018) - Bose, Moumita; Moula, Golam; Begum, Ameerunisha; Sarkar, Sabyasachi
Abstract : The Mo(iv ) bis (dithiolate) complex showed diverse reactions with Me3 SiCN in the presence and absence of a coligand and under protic and aprotic media. Abstract : Cyanide- and isocyanide-bound molybdenum complexes containing maleonitriledithiolate (mnt = 1, 2-dicyanoethylenedithiolate = S2 C2 (CN)2 ) as coligands were prepared from the synthon [Et4 N]2 [Mo IV O(mnt)2 ] (1 ) as [Et4 N][(PPh3 )(mnt)2 3− ˙Mo III (μ-CN)Mo III (PPh3 )(mnt)2 3− ˙] (3 ), [Et4 N][Mo III (PPh3 )(CN)(mnt)2 3− ˙]·CH2 Cl2 (4 ), and [Mo III (CNSiMe3 )2 (mnt)2 3− ˙](5 ) using trimethylsilylcyanide (Me3 SiCN). Triphenylphosphine (PPh3 ) was used as a blocking group and also as a competing ligand to cyanide to control the geometry and reactivity for forming the cyanide-bridged molybdenum dimer3 or with terminal cyanide for the monomer4 . The known tetramer [Et4 N]4 [MoIII4(μ-CN)4 (mnt)8 ] (2 ) formed in the absence of PPh3 showed a remarkable reaction with the excess Me3 SiCN, where the monomeric species [Mo III (CNSiMe3 )2 (mnt)2 ] (5 ) was formed with Me3 SiNC coordination. Overall, the Mo(iv ) bis (dithiolate) complex showed diverse reactions with Me3 SiCN in the presence and absence of the coligand PPh3 and under protic and aprotic media. The precursor molybdenum complex in the IV oxidation state was reduced to the III state in the complexes3, 4, and5, where one of the coordinating chelating ligand mnt 2− was oxidized to mnt 1− ˙. This chemistry was supported by the EPR, electrochemical studies and X-ray crystallography results and corroborated by the DFT level of calculations. The complexes3 and4 were blue-emitting materials with a long lifetime in the millisecond range. Further DFT and TD-DFT calculations were carried out to understand the electronic states and the origin of the electronic absorptions.